The eruption of Vesuvius in AD 79 and the death of Gaius Plinius Secundus - Francois P. Retief; Louise Cilliers (Acta Theologica)
The effect of the volcanic eruption of Vesuvius in AD 79, which led inter alia to the death of Pliny the Elder, is reviewed. Pliny, the admiral of the Roman imperial fleet, wished as scientist to witness the event from close by and set sail in the direction of Vesuvius, but got trapped in Stabiae, a few kilometers from Pompeii, where he died together with thousands of inhabitants of nearby villages. Various reasons have been advanced to account for his death (asphyxiation caused by respiratory problems, carbon dioxide poisoning, heart failure, advanced coronary sclerosis). Basing our findings on the description of the catastrophe in the letters of his nephew, the younger Pliny, we believe that the most probable diagnosis which also fits his description of his uncle’s behaviour and symptoms during his last hours, is that of acute and fatal bronchoconstriction in a chronic asthmatic.